Willingness to Pay for Improving Household Solid Waste Management in Vietnam - Chinh, Phan C.; Hung, Nguyen T.Q.; Ky, Nguyen M.; Ai, Nguyen T.L.; Tam, Nguyen M. (Applied Environmental Research, 2021)
Management of solid waste is a major challenge in urban areas of most parts of the world, especially in developing countries. The study aimed to determine and estimate the willingness to pay (WTP) of the selected households for the improvement of solid waste management in Vietnam. The research evaluated WTP of household solid waste in case studies in Bien Hoa and My Tho cities using contingent valuation method (CVM). The data were collected through a closed-ended questionnaire survey and interviews with 200 households. The results showed that the most willingness to pay was equal to 10,000 and 15,000 VND per month. The respondents were willing to pay in Bien Hoa and My Tho with an average of 14,450 VND (0.63 USD) and 13,000 VND (0.56 USD) per month, respectively. Regression model identified influential factors on WTP of households in the two cities of Vietnam. The factors that significantly influence households’ WTP were monthly household income, education of respondents, age, occupation and solid waste volume (p<0.05). The results of this study can be used for the urban planning and implemented the sustainable development process in Bien Hoa and My Tho cities.